2021
DOI: 10.3390/life11121424
|View full text |Cite
|
Sign up to set email alerts
|

Pillars and Gaps of S-Nitrosylation-Dependent Epigenetic Regulation in Physiology and Cancer

Abstract: Nitric oxide (NO) is a diffusible signaling molecule produced by three isoforms of nitric oxide synthase, which release NO during the metabolism of the amino acid arginine. NO participates in pathophysiological responses of many different tissues, inducing concentration-dependent effect. Indeed, while low NO levels generally have protective effects, higher NO concentrations induce cytotoxic/cytostatic actions. In recent years, evidences have been accumulated unveiling S-nitrosylation as a major NO-dependent po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 169 publications
0
2
0
Order By: Relevance
“…By adding a nitrosyl group (NO-) to reactive cysteine thiols, SNO can profoundly influence protein-protein interactions and subsequent modifications, such as phosphorylation, acetylation, ubiquitination, and disulfide bond formation [ 2 ]. This regulatory mechanism plays a multifaceted role in protein stability, transcriptional regulation, DNA damage repair, cellular growth, and apoptosis [ [4] , [5] , [6] ]. In addition, research has demonstrated that SNO not only acts as a scavenger of nitric oxide (NO), preventing its interaction with reactive oxygen species (ROS) but also serves to protect cysteine thiols from ROS-mediated oxidation [ 7 ]; thus, it has been considered as an emerging paradigm of redox signaling protecting cells against oxidative stress in the hearts.…”
Section: Introductionmentioning
confidence: 99%
“…By adding a nitrosyl group (NO-) to reactive cysteine thiols, SNO can profoundly influence protein-protein interactions and subsequent modifications, such as phosphorylation, acetylation, ubiquitination, and disulfide bond formation [ 2 ]. This regulatory mechanism plays a multifaceted role in protein stability, transcriptional regulation, DNA damage repair, cellular growth, and apoptosis [ [4] , [5] , [6] ]. In addition, research has demonstrated that SNO not only acts as a scavenger of nitric oxide (NO), preventing its interaction with reactive oxygen species (ROS) but also serves to protect cysteine thiols from ROS-mediated oxidation [ 7 ]; thus, it has been considered as an emerging paradigm of redox signaling protecting cells against oxidative stress in the hearts.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of cancer, the influence of NO extends to cell cycle, apoptosis, mitogenic pathways, angiogenesis, invasion, and DNA integrity [27,28]. Thanks to its gaseous nature [29], NO can diffuse through cellular membranes, affecting tumor cells' phenotype and behavior [30,31], as well as tumor microenvironment (TME) [32].…”
Section: Introductionmentioning
confidence: 99%